Impact of wave breaking on upper‐ocean turbulence. Issue 2 (25th February 2017) - Cai, Yongqing; Wen, Yuanqiao; Wu, Lichuan; Zhou, Chunhui; Zhang, Fan
Abstract: Previous studies have demonstrated that surface wave breaking can impact upper‐ocean turbulence through wave‐breaking‐induced turbulence kinetic energy (TKE) flux and momentum flux. Wave‐breaking‐induced momentum flux decays approximately exponentially with depth, and the decay exponent depends on both the wind speed and wave age. With increasing wave age, the decay speed of wave‐breaking‐induced momentum flux first decreases, reaching a minimum around a wave age of 16, and then increases. In this study, a wave‐breaking‐induced momentum flux parameterization was proposed based on wave age and wind‐speed dependence. The new proposed parameterization was introduced into a one‐dimensional (1‐D) ocean model along with a wave‐age‐dependent wave‐breaking‐induced TKE flux parameterization. The simulation results showed that the wave‐breaking impact on the ocean mainly affected the upper‐ocean layer. Adding the wave‐age impact to the wave‐breaking‐induced TKE flux and momentum flux improved the 1‐D model performance concerning the sea temperature. Moreover, the wave‐breaking‐induced momentum flux had a larger impact on the simulation results than the wave‐breaking‐induced TKE flux. Key Points: Wave‐breaking‐induced momentum flux decays approximately exponentially with water depth, and the decay coefficient depends on wave age and wind speed Adding wave‐age‐dependent wave‐breaking‐induced fluxes improves the 1‐D ocean model performance, especially under high‐resolution conditions Wave‐age‐dependent wave‐breaking‐induced momentum flux has a larger impact on the simulation results than wave‐age‐dependent wave‐breaking‐induced turbulence kinetic energy flux